1988
DOI: 10.1192/bjp.153.2.226
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study of Violent Incidents in a Special Hospital (Rampton)

Abstract: A six-month prospective study of violent incidents was carried out in a Special Hospital (Rampton). Comparisons were made with results from earlier studies in general psychiatric hospitals. As might be expected, incidents occurred more frequently in the Special Hospital. These incidents were also more serious in nature and resulted in greater injury. Although more patients in the Special Hospital were involved in incidents, only a small number of patients accounted for the majority of these. Female patients, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
78
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(90 citation statements)
references
References 24 publications
(14 reference statements)
11
78
1
Order By: Relevance
“…1 Twenty years ago, Larkin et al (1988) used ward-based questionnaires to study incidents of actual physical violence there over a 6-month period; 1144 violent incidents were recorded for the hospital population then of 587 (448 men and 139 women). They found that men were about half as likely to have been violent during the study (132, 30%) as the women (83, 60%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Twenty years ago, Larkin et al (1988) used ward-based questionnaires to study incidents of actual physical violence there over a 6-month period; 1144 violent incidents were recorded for the hospital population then of 587 (448 men and 139 women). They found that men were about half as likely to have been violent during the study (132, 30%) as the women (83, 60%).…”
Section: Introductionmentioning
confidence: 99%
“…The patient population has been reduced and has changed in profi le. At the time of Larkin et al's (1988) study, Rampton Hospital contained nearly 600 patients in four legal categories: mental illness, mental impairment, severe mental impairment and psychopathic disorder. Currently, there is a capacity of 396 beds across fi ve directorates: the National High Secure Healthcare Service for Women in England and Wales, the National High Secure Service for Learning Disabilities, Mental Health, Personality Disorder and Dangerous and Severe Personality Disorder (DSPD).…”
Section: Introductionmentioning
confidence: 99%
“…This finding applies to both community (Bonta et al, 1998) and inpatient settings (Larkin, et al, 1988). Indeed, rates of inpatient aggression have been estimated to be around 10-45% with a median rate of 25% (Monahan, 1992;Daffern et al, 2007).…”
Section: Introductionmentioning
confidence: 79%
“…With regard to gender, women not only carry out far more acts of self-harm than men, although suicide is far more common among the latter (National Confidential Inquiry into Suicide and Homicide by People with Mental Illness 2009), but one study from a high secure hospital (Rampton) suggests that women are also responsible for a disproportionately high rate of violence towards staff and peers (Larkin 1988). This study revealed that although women constituted only a quarter of the patient population, they were responsible for three-quarters of all aggressive incidents against self and others.…”
Section: Rates Of Self-harm and Suicidementioning
confidence: 99%